Hybrid solar desalination systems driven by parabolic trough and parabolic dish CSP technologies: Technology categorization, thermodynamic performance and economical assessment. (15th September 2020) - Aboelmaaref, Moustafa M.; Zayed, Mohamed E.; Zhao, Jun; Li, Wenjia; Askalany, Ahmed A.; Salem Ahmed, M.; Ali, Ehab S.
Highlights: Parabolic trough/parabolic dish-desalination plant designs were critically reviewed. A performance assessment and economic analyses of hybrid desalination plants are analyzed. RO plant powered by parabolic trough is more economical than parabolic trough-MED-TVC plant. Hybrid MED-RO system with parabolic trough is a promising technology. System performance characteristics, challenges, and future strategies are discussed. Abstract: In this review, current status and recent progress in concentrated solar power (CSP) desalination technology has been presented. Special focus has been considered for designs and hybridization configurations, thermodynamic performance assessment, and economic analyses of hybrid solar desalination systems driven by only the parabolic trough, or/parabolic dish CSP systems. Studies that combined solar parabolic trough/dish with different desalination technologies such as multi-effect distillation (MED), reverse osmosis (RO), humidification-dehumidification (HDH), multi-stage flash (MSF), and thermal vapor compression (TVC) either for only freshwater production or for co-generation of power and freshwater are discussed in details. Comparison among the reviewed solar concentrated parabolic trough desalinating systems shows that the MED-TVC system powered by parabolic trough solar field is more appropriate than a parabolic trough-RO combination from a thermodynamic viewpoint. In addition, solar parabolic trough and dish collectors can operate the thermal cycles to drive RO desalination system with lower cost of producing water than the MED process. It can be concluded that adopting parabolic trough CSP-desalination technology was a better option for improving the economic advantages of hybrid CSP-desalination industry than adopting parabolic dish CSP-desalination technology. Furthermore, the hybrid MED-RO system with parabolic trough technology is characterized by high reliability, high freshwater generating efficiency, and low desalination cost. Nevertheless, more theoretical and experimental data are needed to optimize these hybrid systems to gain higher efficiency and lower operating cost in the future.